Methodological Problematics of Purposive and Convenience Sampling: Insights from Graduate Student Researchers - Joseph Aketema (PT. Riset Press International, 2026)
Sampling remains a decisive stage in empirical research, shaping the validity, credibility, and transferability of findings. This study interrogates the methodological problems of purposive and convenience sampling, two widely used non-probability techniques in qualitative and exploratory research. Drawing on evidence from forty graduate researchers across four public universities in Ghana, the study examines their conceptual foundations, practical applications, and implications for reliability, bias, and generalizability. Findings indicate that while purposive sampling enhances depth and theoretical relevance, it is susceptible to researcher subjectivity and selective bias. Convenience sampling, although economical and time-efficient, often weakens representativeness and inferential credibility. The paper further highlights how funding and time constraints significantly shape graduate students’ methodological choices, often compelling them to rely on these approaches. To address these challenges, it recommends adopting flexible yet rigorous research designs that leverage the strengths of both sampling methods without compromising data validity. Institutional support through funding schemes such as the Ghana Education Trust Fund is essential, alongside structured supervisory guidance and realistic research timelines. Additionally, training in cost-effective data collection methods, including digital surveys and virtual interviews, can reduce logistical burdens. The promotion of collaborative research networks and peer support systems is also crucial for resource sharing and improved participant access. Ultimately, the study argues that reflexivity, transparency, and methodological justification are indispensable to ensuring that purposive and convenience sampling do not undermine the quality and credibility of graduate research outcomes.